Energy and Exergy Investigations of a 972mw Based Steam Parameters Thermal Power Plant in Nigeria - Oseme, Okuma Silas; Chukwuekum, Orumgbe; Mafel, Obhuo (Journal of Advanced Industrial Technology and Application, 2022)
The generation of electricity is critical to the expansion of the economy and the improvement of people’s standard of living. Scientists from all over the world find themselves increasingly aware of the impact of power plants as a result of the expanding human population and the ever-increasing demand for dependable sources of energy. The construction of about 95% of power plants is carried out in accordance with energy performance requirements, which take into account only the first law of thermodynamics. It is not possible to use the first equation of thermodynamics to compute the actual effective energy loss since it does not differentiate between the quantity and quality of energy.Calculating energy and exergy based on the properties of the steam was at the focus of the investigation into the energy and exergy efficiency of the plant. According to the findings, an increase in the parameters governing the scalding steam caused an increase in both the system’s efficiency and its enthalpy. The boiler has the highest exergy efficiency (59.66%), whereas the condenser has the highest energy efficiency (48.10%). The investigation proved beyond a shadow of a doubt that the boiler was the principal cause of the system’s irreversibility.